Penilaian Karyawan Terhadap Pengawasan Kinerja Duty Manager Pada Front Office Department - Sanjaya, Putu Putra; Sari, Ni Putu Ratna; Suarka, Fanny Maharani (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2023)
This study discusses the assessment of employees in the Front Office Department on the supervision carried out by the Duty Manager at Four Points by Sheraton Kuta. There are 2 Duty Managers in the Front Office Department who have the duties and responsibilities to supervise employees through 4 stages of supervision. Based on the observations, the Duty Manager has not carried out supervision well enough, especially in providing corrective actions to employees. In improving the supervision provided by the Duty Manager in the Front Office Department, an evaluation from the Front Office Manager is needed which in this evaluation also needs to be added all input or suggestions from employees in the Front Office Department. The purpose of this study is to determine the employee's assessment of the supervision of the performance of the Duty Manager towards the employee and the comparison between the supervision of the Duty Manager in the Front Office Department.This research is located at Jalan Benesari, Banjar Pengabetan, Kuta. The sampling technique used was saturated samples with a sample of 20 people. The research method used in this study is a qualitative descriptive method and uses a Likert scale measurement. The results of this study are employee ratings of Duty Manager A get an average of 3.55 which means agree and while Duty Manager B get a score of 3.76 which means also agree. The comparison results show that the supervision of Duty Manager B is better than Duty Manager A, which can be seen from two indicators, namely the comparison of standards with the performance of employees who score higher, namely 4.02 and indicators of corrective action for Duty Manager B also get a higher score than Duty Manager A is 3,2